KEPEMIMPINAN KEPALA SEKOLAH DI SDN NO. 8 TENGGULI KECAMATAN SAMBAS KABUPATEN SAMBAS - Maskur Syafaruddin; Wahyudi Wahyudi; Aswandi Aswandi (Universitas Tanjungpura, 2017)
AbstaractOne of the components to realize the quality of the school is the Principal Leadership and the quality of services provided to the students so as to produce qualified learners. It is expected that with the improvement of leadership function in the form of moving, guiding, influencing, directing personal school can improve school quality and overcome the obstacles. The focus of this research is Principal Leadership with research questions directed at: How the ability of school principals to mobilize, guide, influence, and direct personal school can improve the quality of school and what obstacles and how the solution to improve quality in SDN No. 8 Tengguli Kecamatan Sajad Sambas Regency ?. Qualitative research method of case study research type. Data collection techniques use observation, interviews, and documents. It's a book of android phones, laptops. The results revealed that the leadership traits conducted by the head of SDN. 8 Tengguli Kecamatan Sajad Sambas Regency such as the ability to move, guide, influence, direct and motivate the personal to improve academic achievement in the institution he leads show that the concept has a tendency in line with that put forward by experts. However, the academic achievement of the school during its last 2 (two) years of leadership has declined because the principal has not mastered the philosophy and social history of the quality program (BERSINAPLAH) conducted by the previous headmaster's leadership. Keywords: Principal Leadership, moving, guiding, influencing, directing